Implementasi Sistem Informasi Manajemen Pendidikan dalam Meningkatkan Pelayanan Sekolah terhadap Masyarakat - Duki; Dicky Putra (ANNAHDLIYAH, 2025)
The research aim to describe 1) Management information system planning in improving school services 2) Implementation of management information systems in improving school services 3) Impact of school services using educational management information systems This research uses qualitative approach with descriptive research type. Data collection was carried out by observing, in-depth interviews and documentation. The results of the research at Ma'arif Vocational High School, Batu City, concluded: 1. Planning for a management information system to improve school services at Ma'arif Vocational School, Batu City, includes: a. background on the importance of management information systems, b. planning involves discussions with the school, c. The principal has a role as a decision maker, d. steps in planning. 2. The implementation of a management information system in improving school services at Ma'arif Vocational School, Batu City, includes: a. The management information system facilitates school administration activities, b. Application features that can assist in conveying information, c. Facilitate the internal and external school community in obtaining information. 3. The impact of school services using an education management information system includes: a. Simplify the process of inputting data, b. Improving school administration services, c. Improving school services to the external school community. From the results of the research above, it can be seen that at least it has been put to good use by the internal and external school community in helping and facilitating their tasks and work. However, the use of all application menu features in improving school services is still not optimal, because school IT technicians are limited in human resources.